2009
DOI: 10.1007/s00421-009-1103-9
|View full text |Cite
|
Sign up to set email alerts
|

One night of sleep deprivation decreases treadmill endurance performance

Abstract: The aim was to test the hypothesis that one night of sleep deprivation will impair pre-loaded 30 min endurance performance and alter the cardio-respiratory, thermoregulatory and perceptual responses to exercise. Eleven males completed two randomised trials separated by 7 days: once after normal sleep (496 (18) min: CON) and once following 30 h without sleep (SDEP). After 30 h participants performed a 30 min pre-load at 60% [VO(2 max) followed by a 30 min self-paced treadmill distance test. Speed, RPE, core tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
4
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 157 publications
(115 citation statements)
references
References 21 publications
9
95
4
7
Order By: Relevance
“…On day two, 29 h into each trial, 90 min walk RPE was similar on CON and SDEP (11 ± 2 and 12 ± 2, P = 0.13); however, RPE was higher than CON after SDEP+ER (15 ± 3, P < 0.01). Time taken to complete the 5 km time trial was longer after SDEP+ER (1961 ± 682 s, P = 0.04) and SDEP (1465 ± 278 s, P = 0.01) than CON (1401 ± 290 s), which agrees with similar studies in our laboratory to examine the effects of sleep loss and energy restriction on endurance performance (Oliver et al 2007;Oliver et al 2009). As on day 1, final 5 km time trial RPE on day 2 was similar on all trials (19 ± 1, P = 0.16), indicating maximal or very near maximal effort during the daily exercise.…”
Section: Trial Sleep Duration and Physical Activitysupporting
confidence: 89%
“…On day two, 29 h into each trial, 90 min walk RPE was similar on CON and SDEP (11 ± 2 and 12 ± 2, P = 0.13); however, RPE was higher than CON after SDEP+ER (15 ± 3, P < 0.01). Time taken to complete the 5 km time trial was longer after SDEP+ER (1961 ± 682 s, P = 0.04) and SDEP (1465 ± 278 s, P = 0.01) than CON (1401 ± 290 s), which agrees with similar studies in our laboratory to examine the effects of sleep loss and energy restriction on endurance performance (Oliver et al 2007;Oliver et al 2009). As on day 1, final 5 km time trial RPE on day 2 was similar on all trials (19 ± 1, P = 0.16), indicating maximal or very near maximal effort during the daily exercise.…”
Section: Trial Sleep Duration and Physical Activitysupporting
confidence: 89%
“…Previous studies report 5-6 days of dietary supplementation with larger doses is necessary to achieve significant increases in muscle Cr levels (Harris et al 1992;Hultman et al 1996). Nevertheless, these are potentially important findings needing replication as sleep deprivation in athletes seems to affect skill performance more than other components of performance (Blumert et al 2007;Edwards and Waterhouse 2009;Oliver et al 2009). …”
Section: Cr Supplementation and Cognitive Enhancement -Effects On Slementioning
confidence: 99%
“…One such stressor that is often added to heat stress in military and athletic settings is sleep loss or deprivation. Several studies have shown that mild sleep loss (24-30 h) detrimentally influences exercise time to exhaustion and thermoregulatory responses (Sawka et al 1984;Born et al 1997;Zhong et al 2005;Oliver et al 2009). Very little is known, however, about the effects of sleep loss on heat shock proteins.…”
Section: Introductionmentioning
confidence: 96%